Evaluasi Kurikulum Pembelajaran Berbasis Kebutuhan Masyarakat: Studi pada Program Sarjana Hukum Ekonomi Syariah - Athief, Fauzul Hanif Noor; Alam, Azhar; Inayati, Nurul Latifatul (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
There are only few numbers of Islamic Economic Law program graduates that have been absorbed as industry practitioners. One of main focus for educational providers is the inadequate curriculum to support its graduates to get involved at any legal profession. Various studies related to the involvement of industry practitioners in curriculum development that are able to increase the absorption of alumni as practitioners are important starting points. This study seeks to solve problems related to what courses are required in a curriculum in order to be able to equip alumni with sufficient competencies. By using the ANP method which requires an industry expert as a respondent, we try to solve this problem. The number of respondents whose opinions were extracted was 10 consisting of practitioners of the legal profession, Islamic financial institutions and professional associations. The results of this study indicate that Legal Competence is the main highlight of the experts. Then Basic Arabic, Financial Statement Analysis, Fatwa Studies, Arbitration and Professional Ethics in the Law became the most important focus for additional courses outside the competencies agreed upon by the entire campus. As for the graduate profile, the most relevant based on the courses offered is Judges. Finally, the development that needs to be done to produce these graduates is Class Lectures.